2019
DOI: 10.1002/tox.22865
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification of H3K4 and oxidative stress are involved in MC‐LR‐induced apoptosis in testicular cells of SD rats

Abstract: Microcystin‐leucine arginine (MC‐LR) is a cyclic heptapeptide, produced by aquatic cyanobacteria such as microcystis, with strong reproductive toxicity which poses greater threat to the reproductive abilities of humans and animals. By exploring the role of trimethylation of histone H3 at lysine 4 (H3K4me3) and the role of oxidative stress in MC‐LR‐induced apoptosis in testicular Sertoli cells in Sprague‐Dawley (SD) rats, this study indicated that MC‐LR increased the expression levels of apoptosis‐related genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the present study, we evaluated the expression of markers for the two enzymes lysine demethylase, responsible for the removal of methyl radicals from the H3, KDM3A, and KDM1AX1. The KDM3A decreases gene silencing, including those related to the inhibition of primordial follicle activation and the induction of apoptosis ( 43 45 ). The relative mRNA expression levels for KDM3A and KDM1AX1 were increased in anethole and EUG 40 treatments when compared to the non-cultured control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we evaluated the expression of markers for the two enzymes lysine demethylase, responsible for the removal of methyl radicals from the H3, KDM3A, and KDM1AX1. The KDM3A decreases gene silencing, including those related to the inhibition of primordial follicle activation and the induction of apoptosis ( 43 45 ). The relative mRNA expression levels for KDM3A and KDM1AX1 were increased in anethole and EUG 40 treatments when compared to the non-cultured control.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the higher rates of follicle survival and activation observed in the EUG 40 may be explained by the silencing of pro-apoptotic genes as well as genes related to the maintenance of primordial follicle quiescence. To date, studies have shown that decreased H3K4me3 levels lead to a reduction in the expression levels of pro-apoptotic genes [Bax, Bad and Bid ( 44 , 45 )].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte apoptosis occurs in the pathological process of various liver diseases. Meanwhile, apoptosis is the most common injury caused by MC‐LR 44–46 . Bcl‐2 family members may regulate apoptosis by influencing the permeability of mitochondrial outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, apoptosis is the most common injury caused by MC-LR. [44][45][46] Bcl-2 family members may regulate apoptosis by influencing the permeability of mitochondrial outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Some speci c compounds have been found that might in uence the level of epigenetic modi cation (Liu et al, 2020a). For example, 5-deoxy5methylthiosine (MTA) is a speci c inhibitor of H3K4 methylation, which mainly inhibits H3K4 methylation, especially trimethylation (Yuan et al, 2019). Methylated histones are recognized by chromatin effectors, which recruit other molecules to alter chromatin structure and function (Taverna et al, 2007).…”
Section: Introductionmentioning
confidence: 99%